2021
DOI: 10.3390/ijms22020811
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Time-Course Physiological Responses and Proteomic Analysis of Melatonin Priming on Promoting Germination in Aged Oat (Avena sativa L.) Seeds

Abstract: Melatonin priming is an effective strategy to improve the germination of aged oat (Avena sativa L.) seeds, but the mechanism involved in its time-course responses has remained largely unknown. In the present study, the phenotypic differences, ultrastructural changes, physiological characteristics, and proteomic profiles were examined in aged and melatonin-primed seed (with 10 μM melatonin treatment for 12, 24, and 36 h). Thus, 36 h priming (T36) had a better remediation effect on aged seeds, reflecting in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Proteomics is an important tool that can be used to determine the biological roles and functions of individual proteins that govern grain seed quality and allow for the systematic analysis of complex cellular mechanisms [ 9 ]. Reports of corn proteome expression during the artificial aging period indicate that artificial aging would increase proteases and breakdown stored proteins, and impair metabolism and energy supplies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics is an important tool that can be used to determine the biological roles and functions of individual proteins that govern grain seed quality and allow for the systematic analysis of complex cellular mechanisms [ 9 ]. Reports of corn proteome expression during the artificial aging period indicate that artificial aging would increase proteases and breakdown stored proteins, and impair metabolism and energy supplies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oat, an important annual cereal crop grown worldwide, can provide proteins, soluble fibers (β-glucans), unsaturated fatty acids, vitamins, minerals, and antioxidants [35,36]. It has become increasingly more attractive in recent years due to the discovery of its many health benefits such as lowering cholesterol and reducing glycemic response [37].…”
Section: Introductionmentioning
confidence: 99%
“…It is undeniable that seed germination requires abundant energy and carbon skeletons [8,23,43]. Seeds store oil in the form of TAG in oleosomes to meet the energy demand of heterotrophic-to-autotrophic conversion during seed germination and seedling formation [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…As an effective presowing treatment technique to improve seed vigor, seed priming enables seeds to reach the pregermination stage when the radicle is about to break through the seed coat, thus allowing the seeds to carry out the metabolic process related to germination in advance [7,8]. Studies on a variety of crops have demonstrated that seed priming improves the germination characteristics and promotes seedling growth [9][10][11].…”
Section: Introductionmentioning
confidence: 99%